Bourdieu dan Hubungan Internasional: Konsep, Aplikasi, dan Filsafat Ilmu - Muhaimin Zulhair (Jurnal Transformasi Global, 2016)
This paper attempts to explain the concept of field, habitus, capital, symbolic, doxa and illusio by Pierre Bourdieu, explain Bourdieu’s philosophical position and show the sampling works of IR scholars. This writing will highlight the importance of introducing and amplifiying the mentioned concept of Bourdieu with the purpose reach a wider audience of IR in Indonesia. Therefore, paving the basic path, the explanation will be following the order: the international contemporary setting, Bourdieu’s concepts, sampling works in IR which apllied the concepts, and Bourdieu’s philosophical science position.Keywords: Bourdieu, concept, international, philosophical, sampling